2017
DOI: 10.1111/jgh.13700
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic inulin‐type fructans and galacto‐oligosaccharides: definition, specificity, function, and application in gastrointestinal disorders

Abstract: Prebiotics are non-digestible selectively fermented dietary fibers that specifically promote the growth of one or more bacterial genera in the gastrointestinal tract and thus provide health benefit to the host. The two most investigated prebiotics being the inulin-type fructans and galacto-oligosaccharides. Prebiotic specificity is mediated through speciesspecific gene clusters within saccharolytic bacteria controlled by signaling sensors for various substrates. Prebiotic health benefits are attributed to immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
156
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(165 citation statements)
references
References 30 publications
0
156
0
9
Order By: Relevance
“…Potential effects from dietary therapies may be modulated via use of supplemental probiotic or prebiotic supplementation . For example, 10‐day 16 g fructo‐oligosaccharide supplement in conjunction with the low FODMAP diet increased bacterial abundance, although it did not improve SCFA production .…”
Section: Safety Issues Related To Dietary Therapies In Irritable Bowementioning
confidence: 99%
“…Potential effects from dietary therapies may be modulated via use of supplemental probiotic or prebiotic supplementation . For example, 10‐day 16 g fructo‐oligosaccharide supplement in conjunction with the low FODMAP diet increased bacterial abundance, although it did not improve SCFA production .…”
Section: Safety Issues Related To Dietary Therapies In Irritable Bowementioning
confidence: 99%
“…Separately, a 12-week parallel cross-over trial, which used a β-GOS, showed a dose-dependent stimulation of biidobacteria at 3.5 and 7.0 g/d. Global symptom relief scores were signiicantly improved in the prebiotic group vs. the placebo, including for latulence, bloating, and stool consistency [74,75].…”
Section: Prebiotics and Ibsmentioning
confidence: 96%
“…). These types of GOS are referred to as ‘α‐GOS’ as they consist of α‐linked galactose, α‐linked glucose and a terminal β‐linked fructose (Wilson & Whelan ). Due to the presence of three different bonds, α‐GOS (found within plant foods) have been found to stimulate the growth of a wider range of gut bacterial species than ‘β‐GOS’, which are derived from the enzymatic glycosylation of lactose, contain terminal β‐linked glucose (Goulas et al .…”
Section: Prebiotic Content Of Foodsmentioning
confidence: 99%
“…). Therefore, β‐GOS have predominantly been investigated in human studies rather than plant‐derived α‐GOS (Wilson & Whelan ). Different β‐GOS mixtures can be produced synthetically depending on the source of the β‐galactosidase enzyme used, and evidence suggests that these have differing bifidogenic effects in the human gut (Depeint et al .…”
Section: Prebiotic Content Of Foodsmentioning
confidence: 99%